Multiliteracies Pedagogy. Issue 3 (6th September 2014) - Hepple, Erika; Sockhill, Margaret; Tan, Ashley; Alford, Jennifer
Abstract In addressing literacy in high school education, it is important to foreground the particular issues faced by growing numbers of English Language Learners (ELLs). In our increasingly culturally and linguistically diverse classrooms, this is a matter for all literacy teachers, as well as ELL specialists. In Australia, teachers of ELLs are experimenting with Multiliteracies pedagogy which provides rich opportunities to explore language learning experiences and outcomes that stretch beyond exercises in reproduction in written and oral modes only. This paper documents the practice of a high school teacher who uses a claymation project, producing a movie by stop‐motion filming of clay figures, with a class of low‐level English literacy learners. Drawing on observations of three particular students, the paper outlines a number of possibilities of this approach for English language learners. These include increased individual agency; enhanced engagement through collaboration; and the opportunity to explore various elements of multimodal text design.